Ethical Dilemmas of End of Life Care in Intensive Care Unit : A Literature Review - Arianto, Albertus Budi; Trisyani, Yanny; Emaliyawati, Etika (JURNAL PENDIDIKAN KEPERAWATAN INDONESIA, 2018)
Â ABSTRACTThe end-of-life (EOL) care is the progressive terminal illness, leading to death; that in the situation the nurse have significant role in decision making. In decision making, temporarily, the nurse will experiences the ethical dilemmas, including in intensive care unit (ICU) with any factors resulting in problem in medical decision making. The literature review intends to analyze the description of ethical dilemmas occurred in intensive care unit, especially to the EOL care. A method used is critical review full text of 2007-2018 periods in English langguage. The multiple databases used is PubMed, Proquest and Google Scholar with keyword â€œEnd of Life Careâ€ and â€œNursing Ethic in critical careâ€ and â€œissue End-of-life critical careâ€, and â€œDilemmas Ethic in ICU.â€ The articles selected gradually by using of Appraisal tool of PRISMA and obtained 21 articles. The literature study obtaining 4 themes related to description of the ethical dilemmas in ICU including (1) the ethical principle involved in EOL care at ICU, (2) resource of ethical conflict in ICU, (3) impact of ethical conflict in ICU, and (4) response of nurse in dealing with ethical dilemmas. The discussion of literature review related to the perception of nurse on EOL care; that nurse have important role in medical decision making involving ethical principle in the implementation. it is required further research on exploration of nurse experience on implementation of ethical principle in case of EOL care.ABSTRAKPerawatan end of life (EOL) merupakan suatu perawatan pada penyakit terminal yang bersifat progresif, yang akan berujung dengan kematian, pada kondisi ini perawat mempunyai peran dalam pengambilan keputusan perawatan. Terkadang dalam pengambilan keputusan ini perawat akan mengalami kondisi dilema etik, tak terkecuali di ruangan intensive care unit dimana diruangan tersebut banyak faktor yang mengakibatkan kesulitan dalam pengambilan keputusan medis. Literature reviews ini bertujuan untuk menganalisia gambaran dilema etik yang terjadi di area intensive khususnya pada kasus end of life care. Metode yang digunakan adalah critical review full text dengan rentang tahun 2007-2018 dalam Bahasa Inggris. Multiple database yang digunakan adalah PubMed, Proquest dan Google Scholar merupakan database yang digunakan, dengan kata kunci â€œEnd Of Life Careâ€ and â€œNursing Ethic in critical careâ€ and â€œissue End-of-life in critical careâ€, andâ€œDilema Ethic in ICUâ€. Artikel diseleksi bertahap menggunakan Appraisal tool PRISMA dan didapatkan 21 artikel. Studi literatur diperoleh 4 tema terkait gambaran dilema etik di ruang ICU diantaranya (1) Prinsip etik yang terlibat dalam end of life care di ICU, (2) Sumber konflik etik di ICU, (3) Dampak konflik etik di ICU, dan (4) Respon perawat dalam menghadapi dilema etik. Pembahasan telaah literatur ini terkait persepsi perawat mengenai perawatan end of life, dimana perawat mempunyai peran penting dalam pengambilan keputusan medis yang melibatkan prinsip etik dalam pelaksanaannya. Diperlukan penelitian lebih lanjut mengenai eksplorasi pengalaman perawat terhadap implementasi prinsip etik pada kasus perawatan menjelang ajal.